1999
DOI: 10.1136/jamia.1999.0060134
|View full text |Cite
|
Sign up to set email alerts
|

The Limited Use of Digital Ink in the Private-sector Primary Care Physician's Office

Abstract: Two of the greatest obstacles to the implementation of the standardized electronic medical record are physician and staff acceptance and the development of a complete standardized medical vocabulary. Physicians have found the familiar desktop computer environment cumbersome in the examination room and the coding and hierarchic structure of existing vocabulary inadequate. The author recommends the use of digital ink, the graphic form of the pen computer, in telephone messaging and as a supplement in the examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Speed, fluency and accuracy are necessary in telephone documentation. 2,32,36 Halam's study indicated that telephone contact accounts for 20% of a PCP's workload. 36 Richards indicated that these documentation attributes are necessary to prevent future misunderstandings, which may lead to litigation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Speed, fluency and accuracy are necessary in telephone documentation. 2,32,36 Halam's study indicated that telephone contact accounts for 20% of a PCP's workload. 36 Richards indicated that these documentation attributes are necessary to prevent future misunderstandings, which may lead to litigation.…”
Section: Resultsmentioning
confidence: 99%
“…Concern about typing by physicians is commonly reported but physicians in private practice are equally concerned about inadequate staff typing abilities. 2 A 20% drop in gross collection percentage over the last 15 years in the US has reduced disposable income and has compelled many small practices to use part-time and poorly trained clerical help to record telephone messages. 44 The use of handwriting in the form of digital ink would facilitate staff training and allow for accurate message recording because of the fluency, speed and accuracy of the written language.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations